CD4+ T cells expressing CX3CR1, GPR56, with variable CD57 are associated with cardiometabolic diseases in persons with HIV - Wanjalla, Celestine N.; Gabriel, Curtis L.; Fuseini, Hubaida; Bailin, Samuel S.; Mashayekhi, Mona; Simmons, Joshua; Warren, Christopher M.; Glass, David R.; Oakes, Jared; Gangula, Rama; Wilfong, Erin; Priest, Stephen; et al. (Frontiers in Immunology, 2023)
Persons with HIV (PWH) on long-term antiretroviral therapy (ART) have a higher incidence and prevalence of cardiometabolic diseases attributed, in part, due to persistent inflammation despite viral suppression. In addition to traditional risk factors, immune responses to co-infections such as cytomegalovirus (CMV) may play an unappreciated role in cardiometabolic complications and offer new potential therapeutic targets in a subgroup of individuals. We assessed the role of CX3CR1+, GPR56+, and CD57+ (termed CGC+) T cells in cardiometabolic disease in a cohort of 134 PWH on long-term ART co-infected with CMV. We found that PWH with cardiometabolic disease (non-alcoholic fatty liver disease, calcified coronary arteries, or diabetes) have higher circulating CGC+CD4+ T cells compared to metabolically healthy PWH. The traditional risk factor most correlated with CGC+CD4+ T cell frequency was fasting blood glucose, and starch/sucrose metabolites. While unstimulated CGC+CD4+ T cells like other memory T cells depend on oxidative phosphorylation for energy, they exhibited higher expression of carnitine palmitoyl transferase 1A than other CD4+ T cell subsets, suggesting a potentially greater capacity for fatty acid -oxidation. Lastly, we show that CMV-specific T cells against multiple CMV epitopes are predominantly CGC+. Together, this study identifies a potential role for CGC+ CMV-specific T cells in the development of cardiometabolic disease among PWH and supports additional studies to evaluate whether anti-CMV therapies could reduce disease risk in some individuals.